2011
DOI: 10.1021/la102606k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polymer Deposition Method on Thermoresponsive Polymer Films and Resulting Cellular Behavior

Abstract: Poly(N-isopropyl acrylamide) or pNIPAM is a thermoresponsive polymer that is widely studied for use in bioengineering applications. The interest in this polymer lies in the polymer’s unique capability to undergo a sharp property change near physiological temperatures, which aids in the spontaneous release of biological cells from substrates. Currently, there are many methods to deposit pNIPAM onto substrates, including atom transfer radical polymerization (ATRP) and electron beam ionization. Each method yields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…[1519] Their magnetic susceptibility enables MRI monitoring, tracking and quantification of delivery of these chemo-drug-loaded pMNCs to targeted tissues. [2022] In the present study, we synthesized Dox loaded pMNCs (Dox-pMNCs) and characterized Dox drug release kinetics and MR contrast effects. Then, Dox-pMNCs were combined with iodinated oil as a possible translational form to mirror routine clinical practice (Dox-pMNCs combined with iodized oil) and delivered to liver tumors via hepatic artery in the rabbit liver tumor model.…”
Section: Introductionmentioning
confidence: 99%
“…[1519] Their magnetic susceptibility enables MRI monitoring, tracking and quantification of delivery of these chemo-drug-loaded pMNCs to targeted tissues. [2022] In the present study, we synthesized Dox loaded pMNCs (Dox-pMNCs) and characterized Dox drug release kinetics and MR contrast effects. Then, Dox-pMNCs were combined with iodinated oil as a possible translational form to mirror routine clinical practice (Dox-pMNCs combined with iodized oil) and delivered to liver tumors via hepatic artery in the rabbit liver tumor model.…”
Section: Introductionmentioning
confidence: 99%
“…A perturbation in the exocytosis response of cells is revelatory of this perturbation in ways that can, for instance, be measured by histological studies or carbon-fibre microelectrode amperometry (CFMA), as observed by Reed et al [10]. In this study, the introduction of PNIPAM (through plasma deposition or spin coating) on surfaces have shown to slow down the cell exchange between vesicles and extracellular space.…”
Section: Surfaces and Bioadhesionmentioning
confidence: 64%
“…In addition, it was shown that plasma-deposited PNI-PAM shows greater cell adhesion than e-beam coated PNIPAM [10]. These results emphasized the importance of the method used for surface modification.…”
mentioning
confidence: 89%
See 2 more Smart Citations